Two-year Clinical Evaluation of IPS Empress II Ceramic Onlays/Inlays - TAĞTEKİN, DİLEK; YANIKOĞLU, FUNDA (OPERATIVE DENTISTRY INC, 2009)
The stronger the ceramic material, the longer the restoration stays in the mouth. The current study evaluated the two-year clinical performance of a strong ceramic system, IPS Empress II, with increased strength on onlay/inlay restorations of molars. Teeth from 35 patients, including three premolars and 32 molars, were prepared for 28 onlay and seven inlay restorations with IPS Empress II ceramics. The restorations were cemented with a highly viscous, dual-curing luting composite cement (Bifix) and evaluated by two examiners using USPHS criteria at baseline (one week following insertion), six months, one year and two years. The baseline scores and recalls were assessed by Wilcoxon signed rank test. Statistically significant marginal discoloration at the Bravo level was found at the 12- and 24-month recalls (p=0.046). One debonding was statistically insignificant. No changes were observed with respect to anamnesis, such as any symptom from the TMJ or masticatory muscles. No restorations were replaced due to hypersensitivity or were missing at the two-year evaluation. Any wear on the restoration, antagonist tooth or any changes of proximal contacts were not observed. IPS Empress II Ceramics were found to be appropriate as onlay/inlay restorations for clinical use under the conditions of the current study.
Keywords: DIRECT COMPOSITE INLAYS; DIRECT RESIN COMPOSITE; GLASS-IONOMER; FOLLOW-UP; RESTORATIONS; LEUCITE; PERFORMANCE; DENTISTRY; STRENGTH; SYSTEMS